Pendekatan Konseling Islam dalam Menanggulangi Remaja yang Sering Mengkonsumsi Minuman Keras - Saifullah; M. Syakur (Maddah : Jurnal Komunikasi dan Konseling Islam, 2022)
The promiscuity of men and women, drinking, drinking, free sex (free sex) and consuming drugs by teenagers today is one of the causes of wrong association. So that if it is not noticed it will result in mental and physical damage and social inequality in the surrounding community. The purpose of this study was to describe the process of Islamic counseling approach by KH. Ali Khaidar in dealing with teenagers who often consume liquor, the research method used is qualitative research methods, as stated by Bogdan and Taylor (975:5) that qualitative research is a procedure for producing descrip- tive data in the form of written or spoken words from people. -people and behavior that can be obser- ved, the results of the study that in the Islamic counseling approach carried out by KH. Ali Khaidar in tackling teenagers who often consume liquor (1) provides regular religious counseling, (2) provi- des sports programs, this program counselors can see firsthand the client’s physical, psychological and emotional conditions (3) provide entertainment interludes (refreshing) and ( 4) provide skills as a provision of the client’s economic life in the future.